Politics of Urbanscape: Transfiguring the Image of Kolkata. (2016) - Pal, Shreyasi
Abstract: The claim of aesthetic modernity arriving before social modernity (1) is being investigated with reference to 'intense experiments of city-making' in Kolkata. This brings into focus the socio-political inclination of packaging cities to fit a 'global image of efficiency'. Here a deliberate attempt is made to look for specific geo-political appropriation and/or reproduction and/or rejection of both the global and the traditional aesthetic- thus identifying role of aesthetic convictions of the masses, the bourgeoisie and the State, in Asian experiments of worlding cities (2) . The recent tendency in urban studies to locate the geography of authoritative knowledge in specific cases of the Global South is the context of this study (2). The paper would touch upon three beautification projects of Kolkata, at different stages of the post 90-s neo-liberalization era. The subversive claims of the politically conscious masses juxtaposed with the refusal of middle-class global aspirations to remain in the 'waiting rooms of history' (3) and simultaneous knee-jerk policies to compete for global capital provide an interesting case. Kolkata, both suffering from and celebrating its poignant urbanscape- presents a specific referent of how 21 st century Indian cities are not just borrowing Western urban aesthetics but are 'inevitably home-grown' in their construction of appropriate aesthetics. The attempt here is limited to an examination of the desired image of the city, politically defined but socially negotiated, as a locus of possibilities, thus recognising the creativity and violence of space-making in Kolkata as a source of broadly relevant urban theory.